(untitled) - CHANDRA LAKSANA, AFRIT (Jurnal Ilmu Manajemen (JIM), 2013)
Any organization or company need for policies that protect their resources, particularly human resources (Human Resource). Human resources in any organization, whether for-profit or non-profit organizations need a policy to manage their human resources in order to work effectively according to the purpose, vision and mission of the organization. The purpose of this research was to examine and analyze the influence of the implementations safety and health programs and productivity. This research used a saturated sampling method to take sample. By selected the from the population in the operational area of some 60 people. Based on the result of data analysis, it could be concluded that this research doesn’t occur the classical assumptions such as normality, autocorrelation, and heterokedasticity. With still much debate over the implementation of corporate safety, the authors are interested in doing this research. besides due to the importance of consideration of the application of Safety and Healthy Programs and work productivity in an enterprise, the gap results of previous studies (research gap) of some researchers also underlie the need for research Keyword: safety, healthy, productivity, safety and health programs